PERCEPTION OF REPRODUCTIVE AGE WOMEN ON DYSMENORRHOEA IN A LOCAL GOVERNMENT AREA OF EKITI -STATE, NIGERIA - I.C.C., Ajewole; S. A, Babalola (International Journal of Research -GRANTHAALAYAH, 2022)
This research work on the perception of women of reproductive age on dysmenorrhoea in Emure Local Government of Ekiti State. It is a descriptive study. Respondents were selected through simple random sampling technique from the five communities and total sample size of the one hundred (100) was used for the study. Instrument used was a structured questionnaire. Methods: The target population used for the study comprised of one hundred and Ten female youths residing in selected areas of Emure Local Government Area of the State.sampling Technique adopted was simple Random Sampling to select five communities out of eighteen communities that made up the LGA.Female youths 11 t0 49years , who were participants were randomly selected from each community of study.The research Instrument used was a structured questionnaire. Out of the one hundred and ten copies administered, one hundred copies were retrieved which represent ( 90%) of the population. Ethical approval was sought from the National Open University of Nigeria, Ado-Ekiti. The respondents were verbally addressed and confidentiality was assured Data was analyzed manually and finding revealed that 57% related to the causes of dysmenorrhoea to intake of sugary foods. 34% use drugs like aspirin, ibuprofen etc. to relieve menstrual pain and 36% had adequate rest. On the effects of menstrual pain on education and health, 49% said body weakness due to excessive blood loss, reduced appetite for food (34%) and increased urination (11%). Prevention of menstrual pain according to study is mainly by avoiding sugary and fatty foods (57%). On the perception of menstrual pain, 53% indicated that the pain is normal before child birth, (61%) said it is hereditary. In conclusion, there is need for more enlightenment on how to cope effectively with the pain especially on measures to reduce the intensity in order to promote good reproductive health among female.